Clinical Effect of Extracorporeal Shock Wave on Hand Function Recovery after Conservative Therapy of Colles Fracture - Chao ZHANG; Bin HE (康复学报)
Objective:To evaluate the clinical efficacy of extracorporeal shock wave therapy (ESWT) on the hand function recovery on patients with Colles fracture after conservative therapy.Methods:A total of 24 patients with Colles fractures who had treated with manipulative reduction and gypsum bandage fixation were randomly divided into ESWT group and control group, with 12 cases in each group. The control group was trained with general hand function recovery rehabilitation approach, the ESWT group was treated with extracorporeal shock wave therapy on the basis of the control group.Results:After treatment, the AROM and TAM scores of wrists of the two groups were significantly improved than those before treatment, with statistically significant differences (P<0.05), ESWT group improved more significantly than the control group (P<0.05);the VAS scores and DASH scores of both groups were significantly lower than those before treatment, with statistically significant differences (P<0.05), the scores of ESWT group reduced more significantly than the control group (P<0.05).Conclusion:Combined with hand function rehabilitation, extracorporeal shock wave can improve joint mobility, hand function and activities of daily living more effectively after conservative treatment of Colles fractures, and can effectively reduce patients' edema and pain.